2019
DOI: 10.1002/acn3.50833
|View full text |Cite|
|
Sign up to set email alerts
|

Biomarkers for REM sleep behavior disorder in idiopathic and narcoleptic patients

Abstract: To search for discriminating biomarkers, 30 patients with idiopathic rapid‐eye‐movements sleep behavior disorder (iRBD) were compared with 17 patients with RBD within narcolepsy type 1. Both groups underwent extensive examinations, including skin biopsy searching for phosphorylated α‐synuclein deposits and whole‐night video‐polysomnography. Skin biopsy was positive for phosphorylated α‐synuclein deposits in 86.7% of iRBD patients and in none of narcoleptic patients. The analysis of video‐polysomnographic motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…30,31 More recently, the detection of phosphorylated alpha-synuclein from patients with idiopathic rapid eye movement sleep behavioral disorder suggests that early detection is an achievable goal. 16,32,33 These findings suggest that the need to optimize methodological techniques to maximize rates of early detection will be a critically important technical advance.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 More recently, the detection of phosphorylated alpha-synuclein from patients with idiopathic rapid eye movement sleep behavioral disorder suggests that early detection is an achievable goal. 16,32,33 These findings suggest that the need to optimize methodological techniques to maximize rates of early detection will be a critically important technical advance.…”
Section: Discussionmentioning
confidence: 99%
“…• Nightmares occur both in NREM and REM sleep exhibit complex motor activities during NREM sleep, a characteristic which is not typical in the idiopathic RBD patients. 146 A prospective polysomnographic study over 2 consecutive nights found that 40% of children with narcolepsy type 1 exhibited simple gesturing during NREM sleep and 70% during REM sleep. 147 The prevalence of RBD in adults with narcolepsy type 2, relative to type 1, is believed to be less common, ranging from 0.3 to 15%.…”
Section: Narcolepsymentioning
confidence: 99%
“…The Braak staging system for PD suggests that pathology begins in the peripheral autonomic nervous system or olfactory bulb and then migrates proximally to the amygdala and brainstem and in the more severe cases, to the cerebral cortex (50). This model is supported by some human studies, such as those of multiple groups finding high levels of alpha-synuclein pathology in skin biopsies in early PD and in REM-sleep behavior disorder (RBD) without other clinical evidence of synucleinopathy (20,21,(51)(52)(53)(54). However, the model is not supported by other large autopsy-based studies that find no evidence of peripheral-first synucleinopathy (e.g.…”
Section: Alpha-synuclein Biomarkersmentioning
confidence: 93%